Living with oil and natural gas: a risk perception study among adults in Kansas and Oklahoma - Ramekar, Avantika Anil (Kansas State University, 2020)
Technological advances such as combining hydraulic fracturing and directional drilling (HFDD) have given access to oil and gas reserves previously deemed uneconomical to recover in parts of the U.S. where these resources exist. The oil and gas industry is an important economic contributor for Kansas and Oklahoma. Thus, with untapped oil and gas resources now within economical reach, the Mississippian Limestone Play (MLP) region of Kansas and Oklahoma witnessed a new oil rush in the late 2000s. Amidst the expansion of HFDD, heated controversy about the new technology’s impacts on humans and the natural environment has generated uncertainty about its support or opposition within local communities. Despite the ambiguity, development has continued. For rural areas and small communities in Kansas and Oklahoma, volatile industrial development can increase their vulnerability to related hazards and economic perturbations. With a shortage of environmental risk perception studies about HFDD development and exclusion of social psychological disruption factors in technological risk perception studies, our explanation for different public views about HFDD has perforce been limited. In this dissertation, I draw upon the tradition of risk perception research to investigate risk perception associated with HFDD in the MLP region of Kansas and Oklahoma, and whether environmental risk perception varies spatially. A mixed method approach combining mailed questionnaires and follow-up key informant interviews was used to gather self-reported knowledge, awareness, environmental risk perception, evaluation of benefits and risks, worldviews, sources of information and trust and socio-demographic data, from ten randomly selected counties within the MLP. I build on the theoretical premise that people’s risk perceptions are based on subjective interpretation of information, previous experience, and knowledge, rather than objective information. My results show that despite similarities, regional meanings of the concept of ‘risk’ are tied to an individual’s experience and interactions with their immediate surroundings. Environmental risk perceptions varied spatially for several reasons. These include experiences of the community and individuals with the industry, length of association, knowledge, awareness, and community life experience in addition to trust in local authorities. The finding supports social disruption theory for communities experiencing their first fossil fuel industry, but communities with longer familiarity and experience ended up adjusting better to industrial ebbs and flows. The psychological element of place-based disruption showed a significant relation to risk perception. As respondents’ enthusiasm for HFDD in their communities grew, environmental risk perception decreased. In Kansas, public officials expressed a need for better local financial management for the future and more community awareness programs focusing on legal, technical, and economic aspects of the industry. In Oklahoma, public officials identified better management of investments in infrastructure projects associated with industrial demands. This study recommends inclusion of local risk perceptions and factors contributing to it for effective policymaking. Inclusion of locally sourced, socially constructed knowledge will help in making stronger place-based policy to solve regional issues in a timely and cost-effective way. Collaboration to share knowledge and strategies will help build communities resilient to ebbs and flows of industrial dynamics in the future.
Keywords: Mississippian Limestone Play (MLP); Hydraulic fracturing; Mixed methods; Energy developmentRisk perception